2018
DOI: 10.1002/bjs.10739
|View full text |Cite
|
Sign up to set email alerts
|

Effect of parathyroidectomy on quality of life and non-specific symptoms in normocalcaemic primary hyperparathyroidism

Abstract: Parathyroidectomy mildly improves quality of life and some non-specific symptoms in patients with NcPHPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 21 publications
1
42
0
3
Order By: Relevance
“…Three patients had a calcium level within the normal range at the baseline examination, but all had raised levels before inclusion and no patient was truly normocalcaemic. The presence of non‐specific symptoms and improvements after PTX were found to be independent of baseline calcium levels, supporting the findings reported recently by Bannani and colleagues.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Three patients had a calcium level within the normal range at the baseline examination, but all had raised levels before inclusion and no patient was truly normocalcaemic. The presence of non‐specific symptoms and improvements after PTX were found to be independent of baseline calcium levels, supporting the findings reported recently by Bannani and colleagues.…”
Section: Discussionsupporting
confidence: 90%
“…The majority of these patients are not necessarily included in the international guidelines for treatment of pHPT. A recent prospective multicentre study revealed significant long‐term recovery from non‐specific symptoms overall after parathyroidectomy (PTX) in both normocalcaemic and hypercalcaemic patients with pHPT. Previously, it has not been possible to make predictions on which individuals will experience improvements after PTX.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous observational studies have evaluated the effect of PTX in PHPT using the SF‐36 survey as well as other non‐disease‐specific questionnaires, suggesting improvement in HRQoL . An observational study by Rolighed et al HRQoL, assessed by SF‐36, were reduced in all 8 domains compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…физический компонент состояния здоровья оценивался с помощью опросника SF-36 и было показано его значимое улучшение через 3, 6 и 12 месяцев после операции. Однако в дооперационном периоде с целью коррекции дефицита витамина D назначалась терапия колекальциферолом, что могло дополнительно повлиять на результаты [70].…”
Section: миопатииunclassified